Computational screening of slime mold-derived compounds against NF-κB-inducing kinase (NIK) for potential breast cancer therapy - Volta Kellik Setiawan; Moh Royhan Afnani; Anwar Rovik; Dora Dayu Rahma Turista; Mohammad Indra Pratama (Bioma : Berkala Ilmiah Biologi, 2026)
Breast cancer remains a major global health challenge, particularly due to therapeutic resistance driven by complex molecular mechanisms, including dysregulation of kinase-mediated signaling pathways. One critical target is nuclear factor kappa-light-chain-enhancer of activated B cells inducing kinase, which plays an essential role in tumor progression, inflammation, and resistance to treatment. This study aimed to identify potential natural inhibitors derived from slime mold metabolites using a comprehensive in silico approach. Molecular docking, pharmacokinetic prediction, toxicity assessment, and biological activity analysis were conducted to evaluate two compounds, Cribrarione A and Fuligorubin A, in comparison with a reference drug. The docking results demonstrated that Cribrarione A exhibited strong binding affinity with a binding energy of −8.3 kcal/mol, approaching that of the reference compound (−9.5 kcal/mol), while Fuligorubin A showed moderate affinity (−8.0 kcal/mol). All compounds occupied the catalytic pocket and interacted with key amino acid residues associated with kinase activity. Pharmacokinetic analysis indicated that all compounds met drug-likeness criteria and exhibited favorable absorption profiles with no predicted hepatotoxicity or mutagenicity. Furthermore, biological activity prediction revealed that Cribrarione A has promising anticancer potential through mechanisms involving apoptosis induction and suppression of inflammatory signaling pathways. Overall, these findings suggest that slime mold-derived metabolites, particularly Cribrarione A, may serve as promising lead compounds for breast cancer therapy targeting kinase-mediated pathways, although further experimental validation is necessary.